THE IMPLICATION OF GREEN MARKETING THAT INFLUENCE THE CUSTOMER AWARENESS TOWARDS THEIR PURCHASE DECISION - Yanto Ramli; Dudi Permana; Mochamad Soelton; Swarmilah Hariani; Tantri Yanuar (MIX: JURNAL ILMIAH MANAJEMEN, 2020)
The disposal of plastic waste in the ocean has become a serious issue in Indonesia. There has been plenty of news referring the plastic trash in the Ocean, which has harm and kill lots of sea animals around the ocean and also create unhealthy environment. The intention of this study is to analyze and implement green marketing in fast food restaurants to promote and educate customers referring to the dangers of using plastic products and  control them from the fast food restaurants. This research is to analyze the customer awareness and bahavior towards their purchase decision in relating to green marketing as the intervening variable. The collection of data is done through the distribution of questionnaire to the respondents,thecustomers ofKFC restaurants in Jakarta, Indonesia is the respondent of this research. The method of analysis is based on descriptive and verification research, the sample determination is usingPurposive Random Sampling and the data analysis is using Partial Least Square (PLS). The results show that customer awareness and customer behavior have positive and significant effect towards green marketing and customer behavior has the most significant influence towards green marketing compared to customer awareness. The results show that KFC customers' awareness concerning the plastic waste is still low eventhough they understand the danger of the plastic waste, but gradually their behavior of preventing the plastic products start to increase after implementing green marketing which have educate them concerning the danger of plastic waste and the limitation of plastic products in the restaurants.